A pedagogical model to develop mathematical power on gifted students in Costa Rica - Díaz Obando, Evangelina; Alemán Castillo, Hazel; Hernández Brenes, Carmen (Uniciencia, 2013)
The purpose of this article is to share an experience on the construction of a pedagogical model that allows high school gifted students to develop mathematical power. This model was designed with the intention to offer an alternative to mathematics teachers, so they can teach these students more efficiently. Most of the time, these students are left out in a mathematics classroom. The intention with this model was to generate a learning environment where all students could develop their intellectual potential, in mathematics. This research was conducted in a public high school, located in San José, Costa Rica. It was developed under a qualitative paradigm. The subjects were two students from eleventh grade selected using specific criteria. Other participants were the mathematics teacher and the whole group. In this report we propose a pedagogical model to assist talented students, in the micro-culture of a classroom. T will be documented with evidences coming from focal point students. Finally, there are some recommendations given to different actors from the community of mathematics educators.